Retrovirus Translation Initiation: Issues and Hypotheses Derived from Study of HIV-1 - Yilmaz, Alper; Bolinger, Cheryl; Boris-Lawrie, Kathleen (Current HIV Research, 2006)
Human immunodeficiency virus type 1 (HIV-1) has a small, multifunctional genome that encodes a relatively large and complex proteome. The virus has adopted specialized post-transcriptional control mechanisms to maximize its coding capacity while economically maintaining the information stored in cis-acting replication sequences. The conserved features of the 5' untranslated region of all viral transcripts suggest they are poor substrates for cap-dependent ribosome scanning and provide a compelling rationale for internal initiation of translation. This article summarizes key experimental results of studies that have evaluated HIV-1 translation initiation. A model is discussed in which capdependent and cap-independent initiation mechanisms of HIV-1 co-exist to ensure viral protein production in the context of 1) structured replication motifs that inhibit ribosome scanning, and 2) alterations in host translation machinery in response to HIV-1 infection or other cellular stresses. We discuss key issues that remain to be understood and suggest parameters to validate internal initiation activity in HIV-1 and other retroviruses.
Keywords: unspliced RNA